The English in Rome, 1362-1420 : portrait of an expatriate community - Harvey, Margaret (Margaret M.) (Cambridge studies in medieval life and thought, 1999)
"Centred on a study of the early archives of the Verabile Collegio Inglese in Rome, the predecessor of the English College of today, this book is more than a study of the beginnings of English institutions in Rome. It attempts to place the English community there between 1362, when the first English hospice for poor people and pilgrims was founded, and 1420 in its political, commercial and religious setting. It includes a description of a group of English merchants, with their wives and widows, as well as members of the papal curia in Rome (from 1376), including a study of Cardinal Adam Easton, a well-known scholar and opponent of John Wycliffe."--Jacket